Family Structure and Maternal Depressive Symptoms: A Cross-National Comparison of Australia, the United Kingdom, and the United States - Rasmussen, Kirsten; Sigler, Elizabeth K; Slighting, Sadie; Jarvis, Jonathan A; Dufur, Mikaela; Pribesh, Shana (My University, 2022)
The purpose of this study is to understand the relationship between family structure and maternal depressive symptoms (MDS) in Australia, the United Kingdom, and the United States. Family structures that involve transitions across life’s course, such as divorce, can alter access to resources and introduce new stressors into family systems. Using the stress process model, we examine the links between family structure, stress, resources, and MDS. Using nationally representative data from Australia, the United Kingdom, and the United States and cross-sectional models for each country, we find that family structure may influence MDS differently in the UK than it does in Australia or, especially, the US. Specifically, mothers in the UK who either enter or leave a marriage after the birth of their child experience increased levels of MDS compared with mothers who do not experience a similar transition. These findings demonstrate that the effects of family structure transitions across life’s course may vary according to the country context as well as to the mother’s access to resources and exposure to stress. Considering that the effects of family structure transitions are not universal, this indicates that greater attention should be paid to the country contexts families exist in and the effects that public policies and social safety nets can have on MDS.
Social Sciences
Keywords: Families and relationships; Health and wellbeing